Randomized controlled trial of stress management and resiliency training for depression (SMART-D)-pilot study. - Ashok Seshadri; Matthew Fuller-Tyszkiewicz; Laura Harper; Matthew M Clark; Balwinder Singh; Sherry Chesak; Aparna S Kaur; Jane McGillivray; Mark A Frye (PLoS ONE)
Objective Major Depressive Disorder (MDD) is characterized by high stress sensitivity and unsatisfactory response rates to standard treatments. Stress and depression share a bidirectional relationship. We, therefore, conducted a pilot randomized control trial (RCT) to understand if adjunctive stress management and resiliency training tailored for depression(SMART-D), can improve treatment outcomes in patients with MDD, receiving treatment as usual(TAU) with standard treatments (medications and/or psychotherapy), in real-world clinical settings, compared to a group receiving TAU. Methods Participants with MDD, in a current depressive episode, were randomized to adjunctive SMART-D (delivered by video telehealth over 8 weeks), compared to TAU alone. Random assignment, blinding of raters and statistician were utilized. The primary outcome measure was baseline to end point change in depression [Hamilton Rating Scale for Depression (HAM-D] over a 6-month follow-up period using a mixed model regression analysis. Results 27 participants (mean age 47.9 ± 14 years, female 67%) enrolled in the study (TAU = 14, SMART-D + TAU = 13). Baseline mood ratings were in mild-moderate symptom severity (HAM-D)- SMART-D + TAU = 12.2 ± 6.6, TAU = 13.9 ± 5.7). Linear mixed model analysis showed significant Group*Time interaction for measures of depression (HAM-D) (B = 6.1 (CI = 1.5-10.8, P = .01) and perceived stress (PSS) (B = 5.5(0.5-10.6), p = .03) between the 2 groups at 3 months post follow-up ((HAMD)-SMART-D + TAU = 8.7 ± 4.3 Vs. TAU = 16.1 ± 6.3), but not at 6-months (SMART-D + TAU = 8.1 ± 5.4 Vs. TAU = 12.3 ± 5.5). Conclusions A RCT of 27 adults with MDD provide initial support that an adjunctive resiliency intervention (SMART-D) for patients with MDD may positively impact symptoms of depression and perceived stress, earlier than standard care. A small sample size limits ability to draw firm conclusions. Further investigation is warranted, using larger samples. Clinical Trials Registration I.D.# NCT04388748.